Diagnostic Accuracy of FNAC for Detection of Malignancy in Palpable Breast Lump and its Comparison with Tru-Cut Biopsy - Bashir Ahmad Noor, Muhammad Afham Shahid, Seema Butt, Muhammad Umair Afzal, Ahmal Fawad Zafar, Hafiz Zaheer Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Breast cancer is the commonest malignancy in women worldwide and leading cause of cancer related deaths in women, almost half of these occurring in developing countries. Aim was to know the diagnostic accuracy of FNAC for detection of malignancy in palpable breast lump and its comparison with tru-cut biopsy Methodology: Six months following the publication of this report, researchers in the Surgical Department of Allied Hospital Faisalabad conducted this study. Starting on March 31st, 2019, and running all the way through September 30th, 2019. Allied Hospital Faisalabad's ethics council approved the study's summary, and patients who presented to the hospital's breast clinic with a palpable breast lump met the criteria for inclusion in the research. Across all patients, histopathology was performed on FNAC, tru-cut, and excisional biopsy specimens. H&E staining was performed on both the tru-cut biopsy and tissue specimens from later excision procedures to examine the histological characteristics of the tumor tissue. Results: In our study, out of 190 cases, frequency of malignancy on was recorded in 28.42%(n=54), the diagnostic accuracy of Tru-cut biopsy for detection of malignancy in patients with palpable breast lump taking histopathology examination after excision biopsy (HPE) as gold standard was recorded as 80.33% sensitivity, 96.12% specificity, 90.74% positive predictive value,91.18% negative predictive value and 91.05% accuracy rate, likelihood ratio was calculated as 20.72 and diagnostic accuracy of FNAC biopsy for detection of malignancy in patients with palpable breast lump taking histopathology examination after excision biopsy (HPE) as gold standard was recorded as 70.49% sensitivity, 93.80% specificity, 84.31% positive predictive value, 87.05% negative predictive value and 86.32% accuracy rate, likelihood ratio was calculated as 11.37. Conclusion: As far as diagnostic accuracy for the diagnosis of malignancy in patients with palpable breast lumps, FNAC and Tru-cut biopsy are both good, although Tru-cut biopsy is more accurate than FNAC in terms of detecting the disease. Keywords: Palpable breast lump, malignancy, diagnosis, FNAC, Tru-cut biopsy, diagnostic accuracy